Recognition in the laser location of targets with the same effective scattering surface - Шутко, В. М. (Proceedings of National Aviation University (archive), 2021)
Recognition in the laser location of targets with different volumetric parameters having the same effective scattering surface is considered. This task is to test the hypothesis of belonging a random variable to one of two Erlang distributions of different orde